Korelasi SST, OLR Terhadap Curah Hujan di Wilayah Pesisir Timur Sumatera - Amanda Kurnia Utami; Muhammad Irfan; Hamdi Akhsan (Universitas Nurul Huda, 2025)
This study aims to analyze the influence of sea surface temperature (SST), outgoing longwave radiation (OLR), and the Indian Ocean Dipole (IOD) on rainfall dynamics in the peatlands of East Sumatra’s coast. Data from ERA5 (SST, OLR), BMKG (rainfall), and a calculated IOD index (1982–2024) were analyzed quantitatively using Python and Pearson correlation. Results show SST in the Indian and Pacific Oceans correlates significantly and positively with rainfall (r > 0.6; p < 0.05), confirming the dominant roles of IOD and ENSO. OLR exhibits a strong negative correlation (r < –0.7; p < 0.05), reflecting its inverse relationship with convective activity and rainfall. The IOD index is significantly correlated with rainfall variation, particularly during positive IOD events, which are linked to rainfall deficits and increased peat fire risk. This quantitative analysis provides a basis for predicting rainfall and mitigating peatland fires.